Glossary of Biotechnology and Nanobiotechnology Terms - Eleanor Randall (Issues in Science and Technology Librarianship)
The article reviews the book "Glossary of Biotechnology and Nanobiotechnology Terms," fourth edition, Kimball R. Nill.